2007
DOI: 10.5650/jos.56.457
|View full text |Cite
|
Sign up to set email alerts
|

Components of the Essential Oil from Matteuccia struthiopteris

Abstract: A steam distilled oil obtained from Matteuccia struthiopteris was analyzed by GC and GC/MS. The oil was found to contain 103 volatile components, and (E)-phytol (24.8%), nonanal (15.1%) and decanal (7.6%) as the main compounds. The oil included two aldehydes known as sea-weed like odor, (8Z, 11Z, 14Z)-heptadecatrienal (0.6%) and (8Z, 11Z)-heptadecadienal (0.1%). The most characteristic aroma compound was (6Z)-nonenal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 14 publications
1
13
0
2
Order By: Relevance
“…본 연구에서 사용된 청나래고사리(Matteuccia struthiopteris) 는 우리나라와 일본에서는 어린 잎을 식용하며 [20], 근경은 한 방에서는 협과궐(莢果蕨)이라 하여 청열해독과 양혈지형에 사 용하는 약용식물이다 [1]. 최근에는 청나래고사리 전초의 우수 한 항산화활성이 보고되었으며 [9], chlorogenic acid, L-O-caffeolylhomoserine [13] 및 dolicholes [26] …”
Section: 서 론unclassified
“…본 연구에서 사용된 청나래고사리(Matteuccia struthiopteris) 는 우리나라와 일본에서는 어린 잎을 식용하며 [20], 근경은 한 방에서는 협과궐(莢果蕨)이라 하여 청열해독과 양혈지형에 사 용하는 약용식물이다 [1]. 최근에는 청나래고사리 전초의 우수 한 항산화활성이 보고되었으며 [9], chlorogenic acid, L-O-caffeolylhomoserine [13] 및 dolicholes [26] …”
Section: 서 론unclassified
“…The components of the volatile oils were identified by direct comparison of their mass spectral pattern and retention index (RI) with those published in the literature 16) and by our previous work [17][18][19][20] . The quantitative composition of oils was determined by GC (FID), by assuming the total of all the particular oil to be 100%.…”
mentioning
confidence: 99%
“…Chemically, these compounds belonged to fatty acid derivatives (FADs; 16 substances), aromatics (eight), Table 1. VOCs recorded in the six study species, with numbers representing percentage of amounts relative to all recorded VOCs, as well as indication of previous records of these substances among ferns (based on Briggs & Sutherland 1947;Juliani et al 2004;Cheng & Mao 2005;Naseri et al 2006;Miyazawa et al 2007;Radulovi c et al 2008;Imbiscuso et al 2009;Fons et al 2010;Fletcher et al 2011) and angiosperms (based mainly on Knudsen et al 2006). monoterpenes (ten), sesquiterpenes (one), sulphur-containing compounds (one), irregular terpenes (one) and heterocyclic aldehydes (one).…”
Section: Resultsmentioning
confidence: 99%
“…Although a number of fern species have long been known to be fragrant (already Linnaeus described the species Dryopteris fragrans (L.) Schott), there are few studies of VOCs in ferns, so far covering 26 species in the families Adiantaceae, Anemiaceae, Aspleniaceae, Athyriaceae, Blechnaceae, Dennstaedtiaceae, Dryopteridaceae, Equisetaceae, Lygodiaceae, Pteridaceae, Thelypteridaceae and Woodsiaceae (Briggs & Sutherland 1947;Juliani et al 2004;Cheng & Mao 2005;Naseri et al 2006;Miyazawa et al 2007;Radulovi c et al 2008;Imbiscuso et al 2009;Fons et al 2010Fons et al , 2013Fletcher et al 2011;Froissard et al 2011). In the only functional study to date, Imbiscuso et al (2009) showed that Pteris vittata L. reacts to herbivory by increasing the production of VOCs, in this case mostly consisting of mono-and sesquiterpenes, which are well known defence substances in plants (Par e & Tumlinson 1999;Cheng et al 2007;Mumm et al 2008).…”
Section: Introductionmentioning
confidence: 99%